Inverse Planning in the Cracks of Formal Land Use Regulation: The Bottom-Up Regularisation of Informal Settlements in Maputo, Mozambique. (15th March 2019) - Chiodelli, Francesco; Mazzolini, Anna
ABSTRACT: This paper focuses on a case of 'non-public planning' in an informal neighbourhood of Maputo, Mozambique. Here, several residents undertook some planning duties (e.g. drawing up a detailed plan) in order to regularise their informal dwellings in lieu of the Municipality, due to its inertia. This was an attempt to deal with the shortcomings of urban planning in Maputo, not by flouting the system, but by remoulding it and creating a sort of alternative formality. The detailed analysis of this case is an opportunity for critical reflection on the risks, potentialities and inherent limits of such a form of non-public planning in Mozambique, which we label 'inverse planning'.